TWO NEW SPECIES OF FURCOCERCOUS CERCARIAE FROM FRESHWATER SNAILS IN MALABAR, KERALA - VASANDAKUMAR, M.V.; JANARDANAN, K. P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2005)
Two new species of furcocercous cercariae, Cercaria sp. I Malabar n.sp. found in the thiarid snails. Thiara tubercu'ta and Cercaria sp. II Malabar n.sp. in the lymnaeid snails. Lymnaea luteola, collected from difierer ( freshwater bodies of Malabar, Kerala are described.